2007
DOI: 10.1088/0957-4484/18/45/455304
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray deposition of fullerenes in ultra-high vacuum:in situscanning tunneling microscopy and photoemission spectroscopy

Abstract: Electrospray deposition of fullerenes on gold has been successfully observed by in situ room temperature scanning tunneling microscopy and photoemission spectroscopy. Step-edge decoration and hexagonal close-packed islands with a periodicity of 1 nm are observed at low and multilayer coverages respectively, in agreement with thermal evaporation studies. Photoemission spectroscopy shows that fullerenes are being deposited in high purity and are coupling to the gold surface as for thermal evaporation. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 19 publications
0
55
0
Order By: Relevance
“…Fe 4 H molecules were then deposited in situ by ESD from freshly prepared solutions in tetrahydrofuran and methanol (volume ratio 6:1) with the sample kept at room temperature, using a setup based on the UHV4 system from Molecularspray Ltd., which is described in detail elsewhere. 51 All STM measurements were carried out in constant-current mode using grinded and polished PtIr tips (Nanoscore GmbH) and electrochemically etched polycrystalline tungsten tips, cleaned in UHV by flash annealing. Bias voltages refer to the sample potential with respect to the tip.…”
Section: Nano Lettersmentioning
confidence: 99%
“…Fe 4 H molecules were then deposited in situ by ESD from freshly prepared solutions in tetrahydrofuran and methanol (volume ratio 6:1) with the sample kept at room temperature, using a setup based on the UHV4 system from Molecularspray Ltd., which is described in detail elsewhere. 51 All STM measurements were carried out in constant-current mode using grinded and polished PtIr tips (Nanoscore GmbH) and electrochemically etched polycrystalline tungsten tips, cleaned in UHV by flash annealing. Bias voltages refer to the sample potential with respect to the tip.…”
Section: Nano Lettersmentioning
confidence: 99%
“…The UHV-ESD experimental setup has been described in detail previously 33,34 . To summarize, a solution containing the molecules to be deposited is passed through a stainless steel emitter held at ~2 kV at a typical flow rate of 1 µl min − 1 .…”
Section: Uhv-esdmentioning
confidence: 99%
“…1) on an Au(111) surface with coverages ranging from submonolayer to multilayers. It has recently been shown that UHV-ESD and related spray techniques provide a viable method for the transfer of non-volatile/thermally labile species such as dye molecules and polymers from solution onto surfaces held in UHV [33][34][35][36][37][38][39] ; the development and application of this technique is crucial for the deposition of Mn 12 (acetate) 16 . Images of the adsorbed Mn 12 (acetate) 16 are acquired using an STM operating at room temperature under UHV conditions.…”
mentioning
confidence: 99%
“…9 More recently, we have shown that differential pumping of an ES molecular beam from air to UHV can be used to deposit fullerene molecules from solution onto a Au(111) surface at pressures as low as 1 × 10 -8 mbar for in situ scanning tunneling microscopy (STM) and synchrotron-based electron spectroscopy studies. 10 Although the UHV-ESD of molecules (C 60 ) onto metal substrates has been demonstrated, 10 little is known about how the ES deposition (ESD) process could affect surfaces that have been functionalized by supramolecular networks. The formation of two-dimensional supramolecular structures has been extensively studied, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and it has been shown that such structures may be used to facilitate the production of well-ordered templates with network cavities with dimensions on the order of nanometers.…”
Section: Introductionmentioning
confidence: 99%